The Influence of Brand Image, Product Quality, and Price Discount on Impulse Buying to Skintific Skincare Products : (A Study of Skintific Instagram Followers) - Putri, Nifta Ardilia; Kusumasari, Indah Respati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The beauty industry continues to grow as consumers pay increasing attention to the quality and value of skincare products. This study analyzes the influence of brand image, product quality, and price discounts on impulse buying of Skintific products by involving 100 respondents and multiple linear regression analysis using SPSS 31.0. Data collection was carried out through questionnaires, and data analysis included validity tests, reliability tests, classical assumption tests, linear regression, and hypothesis tests. The results of the study indicate that although brand image does not have a significant effect, product quality and price discounts have a significant contribution in encouraging impulse buying. This confirms that good product quality and attractive price discounts are the main factors that trigger impulse buying of Skintific products